The Influence of Solar Ageing on the Compositions of Epoxy Resin with Natural Polyphenol Quercetin - Latos-Brozio, Malgorzata; Czechowski, Leszek; Masek, Anna (Materials, 2024)
Epoxy resin compositions are used in modern railways, replacing other materials. However, epoxy composites in public transport are subject to many requirements, including that they should be flame retardant and resistant to weather conditions. The aim of the research was to analyse the resistance to solar ageing of epoxy resin composites containing flame retardants and the addition of the natural stabilising substance—quercetin. The homogeneity of the samples (optical microscopy and FTIR spectroscopy) and their thermal stability (TGA thermogravimetry) were analysed. The T5 temperature, which is the initial temperature of thermal decomposition of the samples, was 7 °C higher for the epoxy resin containing quercetin, so the material with polyphenol was characterised by better thermal resistance. Changes in material properties (hardness, surface energy, carbonyl index, colour) after 800 h solar ageing were investigated. The tensile tests on materials were executed for three different directions before and after ageing effect. The samples showed good resistance to degradation factors, i.e., they retained the functional properties (hardness and mechanical properties). However, analysis of carbonyl indices and surface energies showed that changes appeared in the composites after solar ageing, suggesting the beginning of material degradation. An approximately 3-fold increase in the polar component in epoxy resin compositions (from approximately 3 mN/m to approximately 11 mN/m) is associated with an increase in their hydrophilicity and the progress of ageing of the materials’ surface. The obtained results are an introduction to further research on the long-term degradation processes of epoxy resins with plant stabilisers.